Cold hard news - Milliken, Maureen (Purcellville, Va. : S & H Publishing, Inc., 2015)
The snowbanks in a small Maine town start to melt, and the town's secrets begin to emerge.
Maine author.
Keywords: O'Dea, Bernie (Fictitious character) -- Fiction; Franklin County (Me.) -- Fiction; Maine -- Fiction; Detective and mystery fiction